An exploratory study on needs for clinical research training: data from Chinese hospitals - Wei Liu (BMC, 2021)
Abstract Objective Through preliminary investigation of needs for clinical research training, to provide some initial evidence for design and operation of clinical research training programs in China. Methods An online questionnaire containing 23 questions about demographics, current practice of clinical research and needs for clinical research training was formulated to collect data from physicians and researchers in hospital. Convenience sampling was adopted. Results A total of 600 valid questionnaires were collected, including 507 from physicians, 58 from full-time clinical researchers and 35 from full-time basic medical researchers. Results showed that 14 % of the participants never participated in any clinical research, difficulties in data statistics were reported by more than 70 % of participants, and over 50 % reported training needs for cohort and biobank construction, data management and clinical study design. As to the training form, a combined on-line lecture with off-line communication is preferred. As for the content of the training program, strategies for literature reading and grant writing are highly demanded. Conclusions In China, even physicians in top hospitals tend to encounter various difficulties when conducting clinical research. This study highlights the importance of systematic training for future physician scientists in China, with a particular focus on data statistics, cohort and biobank construction and data management.